URGENSI PENDIDIKAN ANTITERORISME DALAM KURIKULUM PENDIDIKAN AGAMA DI INDONESIA - Ahmad Muthohar (Jurnal Forum Tarbiyah, 2011)
The phenomenon of terrorism in Indonesia becomes aserious problem. This is because what is mentioned is not just a politicalor ideological issue, but also related to a narrow understandingof religion by a group that has high religious fanaticism. So that theadherents of terrorism are easily regards others as unbelievers ofIslam, even they have a commit of murder massively. Therefore, it isnecessary to overcome not only the security model of intelligence,but also need to have education efforts, which could counteract asense of ism that grows terror. The solution is, the anti-terrorismeducation is applied through primary education up to college. Religiouseducation in schools proved as the most appropriate media toprovide anti-terrorism education. Religious education is not only pushingpeople beyond religion, but also beliefing it. As a result, educationabout religion needs to enclose universal human insights and hospitality(rahmatan lil alamin). The curriculum used in the Educationof Islamic Religion in schools should also include the concept of jihad,enjoining the concept of amar ma’ruf nahi munkar, and pluralistictheology, so that religious education will instill a spirit of religion to getchildren to carry out righteousness (be religious)